أثر التدوير الوظيفي على أداء العاملين في المؤسسة الإقتصادية دراسة حالة سونلغاز للتوزيع الأغواط - بن شريف رضوان علي مهدي; غريقة نبيل; بن تربح بن تربح (جامعة عمار ثليجي الاغواط, 2022)
This study aimed to find out the effects of job rotation and its dimensions on employee performance among employess of Sonelgaz-Distribution Laghouat division, Where the study targeted a group of Sonelgaz employees to test the validity of our hypotheses through the study questionnaire, which included a set of phrases that included the study’s axes and distributed to a sample of 45 individuals, 39 questionnaires were retrieved and are valid for study. The statistical software SPSS 22 was used to test our hypotheses using the following statistical methods (mean, standard deviation, coefficient of variation, correlation coefficients …), Through this, we reached a set of results, the most important of which is that there is a significant effect of job rotation on the performance of employees of the individuals working in the corporation host of the study at the level of morale at 0,05, that was beacause of job design dimension, but there are no statistically significant differences at the same the level of significance and the same variables as the model of study personal data of the sample members examined representing: (gender, age, academic level, , years of service). In the end some practical suggestions and future prospects for the study were also presented.